Peningkatan Softskill Pengusaha Usaha Mikro Kecil Menengah Dan Pengurus Koperasi - Suci Etri Jayanti. S; Sri Winda Hardiyanti Damanik; Rapat Piter Sony Hutauruk; Rakhmawati Purba; Rumiris Siahaan; Abednego Ketaren; Ayu Zurlaini Damanik (Universitas Majalengka, 2023)
A problem at this time, there are Micro, Small and Medium Enterprises who only rely on the products they sell without seeing and knowing the soft skills that must be owned, as well as cooperative management in the KSP KOPDIT CU New Life Cooperative, Kampung Pon Branch, Serdang Bedagai Regency which still has relatively minimal soft skills, so this can hinder progress in interacting with members and customers, including such as; communicate friendly, manage time well, have high motivation for members and customers, and have good emotional intelligence in dealing with any situation. The purpose of carrying out this community service activity is to implement the Tri Dharma of Higher Education, especially Community Service, provide insight into Cooperative and MSME management strategies, motivate in the development of Micro, Small and Medium Enterprises in terms of management and management (soft skills). The method used in this service activity is to use the lecture method, presenting related materials relevant to this activity. The results show great enthusiasm for the progress of Micro, Small and Medium Enterprises and the Progress of Cooperatives in the future.